2014
DOI: 10.5455/2319-2003.ijbcp20140418
|View full text |Cite
|
Sign up to set email alerts
|

A study to evaluate antioxidant and hepatoprotective activity of aqueous extract of roots of Valeriana wallichii in CCl4 induced hepatotoxicity in rats

Abstract: their folklore claim in the book by Hakim Abdul Wahid (1961) 1 and experimented for potential hepatoprotection in albino rats. It is known as "Tagar" in Hindi and Indian Valerian in English. METHODS The roots of Valariana wellichi was purchased from local herbal dealer. It was identified & authenticated by botanist and a voucher specimen was submitted ABSTRACT Background: Drugs for liver ailments have been important in research, but still the number of drugs acting on various hepatic diseases is very limited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It results in an increased level of liver marker enzymes such as ALP and ALT. The level of biochemical markers such as cholesterol, bilirubin, and triglycerides (Chen et al, 2012;Syed et al, 2014). The results of current study demonstrated that AgNPs and chicory formulation extract possessed remarkable hepato-protective potential (Table 3).…”
Section: Discussionmentioning
confidence: 68%
“…It results in an increased level of liver marker enzymes such as ALP and ALT. The level of biochemical markers such as cholesterol, bilirubin, and triglycerides (Chen et al, 2012;Syed et al, 2014). The results of current study demonstrated that AgNPs and chicory formulation extract possessed remarkable hepato-protective potential (Table 3).…”
Section: Discussionmentioning
confidence: 68%
“…[69] Antioxidants are reducing agents which inhibit the oxidation of other molecules and can be used not only to prevent but also to treat health complications of metabolic syndrome and atherosclerosis. Experimental studies showed that piperine, [70] P. anisum Lin seeds, [71] A. graveolence Lin seeds, [72] V. wallichii, Lin rhizome [73] and A. cepa Lin bulb [44] reduce HFD-induced oxidative stress to the cells. The antioxidant activity of these drugs might be due to the polyphenolic compounds present in these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…was given 4 on Day1 and Day 4 at 9:00 am. Standard drug used was silymarin, given in a dose of 50 mg/kg/day by oral route for a period of 14 days (Syed et al, 2014). The test drugs dissolved in distilled water were given by oral route at 1:00 pm for a period of 14 days simultaneously with CCl treatment.…”
Section: Hepatotoxicity Inductionmentioning
confidence: 99%
“…Carbon tetrachloride (CCl ) induced hepatic damage raised the 4 level of enzymes as serum AST, ALT, ALP and Total serum bilirubin and percentage of hepatoprotection against CCl 4 induced injury was calculated(Syed et al, 2014). Silymarin provided highest percentage of hepatoprotection by reducing AST, ALT, ALP and total bilirubin against CCl induced liver 4 injury.…”
mentioning
confidence: 99%